Analisis Perbandingan Short dan Long TE Terhadap Spektrum Metabolit MRS Klinis Tumor Otak - Naibaho, Larasati Putri; Kuswoyo, Heri; Sriyatun, Sriyatun; Tarigan, Asumsie; Anwar, Khairil (Lontara Journal of Health Science and Technology, 2025)
MR Spectroscopy (MRS) can help determine the ratio of brain metabolite spectrum results, in diagnosing brain disorders, especially brain tumors. In MRS, the use of different Time Echo (TE) parameters will affect the results of the metabolite spectrum obtained, as well as the signal intensity at different peak and ratio values. MRS can be performed using short and long TE. This study aims to analyze the differences in peak values in the spectrum of choline, creatine and NAA metabolites and to analyze the comparison of MRS metabolite spectrum results using different TE value variations. The type of research is quantitative analytic with data collection methods using observation, experiments, measurements and literature studies. From the results of the research that has been done, it can be concluded that the use of different short and long TEs affects the results of the spectrum graph, affecting different peak values and ratio values. Both cannot be mutually exclusive, because they have their respective roles in establishing a diagnosis, so the use of this TE variation must be combined in order to establish a diagnosis.